2021
DOI: 10.3390/molecules26082184
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Excitonic Transition Energy and Enhanced Electron-Phonon Coupling in Layered Ternary SnS2-xSex Semiconductors with Fully Tunable Stoichiometry

Abstract: In this study, a series of SnS2-xSex (0 ≤ x ≤ 2) layered semiconductors were grown by the chemical–vapor transport method. The crystal structural and material phase of SnS2-xSex layered van der Waals crystals was characterized by X-ray diffraction measurements and Raman spectroscopy. The temperature dependence of the spectral features in the vicinity of the direct band edge excitonic transitions of the layered SnS2-xSex compounds was measured in the temperature range of 20–300 K using the piezoreflectance (PzR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…EDX mapping (Figure a) showed an equal distribution of tin and selenium, and also in the case of the ternary particles, sulfur is found within the particles. The powder X-ray diffraction data (Figure b) corresponded to SnSe 2 ( P 3̅ m 1), although a slight shift toward larger diffraction angles can be observed for SnS 0.13 Se 1.79 (Figure c), which is probably due to the incorporation of a smaller sulfide anion, which is in accord with other reports. , …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…EDX mapping (Figure a) showed an equal distribution of tin and selenium, and also in the case of the ternary particles, sulfur is found within the particles. The powder X-ray diffraction data (Figure b) corresponded to SnSe 2 ( P 3̅ m 1), although a slight shift toward larger diffraction angles can be observed for SnS 0.13 Se 1.79 (Figure c), which is probably due to the incorporation of a smaller sulfide anion, which is in accord with other reports. , …”
Section: Resultssupporting
confidence: 90%
“…In pure SnS 2 , the Sn–S A 1g mode can be observed at 317 cm –1 . Yu et al and Lin et al showed that in SnS x Se 2– x alloys the Sn–S A 1g mode is shifted toward lower wavenumbers with a decrease in intensity, if the selenium content is increased. , The Sn–S E g mode expected , below 202 cm –1 could not be observed due to its low intensity, when compared to the Sn–S A 1g mode in general and its overlapping position with the Sn–Se A 1g mode.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the Joint Committee on Powder Diffraction Standards (card No. 23-0677 and 89-2939) and previous publications [ 27 , 47 , 48 ], the obtained XRD patterns reveal the hexagonal lattice configuration, which could be 1T or 2H, for SnS 2 and SnSe 2 with lattice parameters a = b = 3.6486 Å and c = 5.8992 Å for SnS 2 and a = b = 3.811 Å and c = 6.137 Å for SnSe 2 .…”
Section: Resultssupporting
confidence: 61%